Magnetism-induced topological transition in EuAs3 - Cheng, Erjian; Xia, Wei; Shi, Xianbiao; Fang, Hongwei; Wang, Chengwei; Xi, Chuanying; Xu, Shaowen; Peets, Darren C.; Wang, Linshu; Su, Hao; Pi, Li; Ren, Wei; et al. (Nature communications, 2021)
The nature of the interaction between magnetism and topology in magnetic topological semimetals remains mysterious, but may be expected to lead to a variety of novel physics. We systematically studied the magnetic semimetal EuAs 3 , demonstrating a magnetism-induced topological transition from a topological nodal-line semimetal in the paramagnetic or the spin-polarized state to a topological massive Dirac metal in the antiferromagnetic ground state at low temperature. The topological nature in the antiferromagnetic state and the spin-polarized state has been verified by electrical transport measurements. An unsaturated and extremely large magnetoresistance of ~2 × 10 5 % at 1.8 K and 28.3 T is observed. In the paramagnetic states, the topological nodal-line structure at the Y point is proven by angle-resolved photoemission spectroscopy. Moreover, a temperature-induced Lifshitz transition accompanied by the emergence of a new band below 3 K is revealed. These results indicate that magnetic EuAs 3 provides a rich platform to explore exotic physics arising from the interaction of magnetism with topology. Magnetic topological materials have a variety of interesting properties, but very few material realizations exist. Here, the authors report a topological nodal-line semimetal and a topological massive Dirac metal phase in EuAs 3 and demonstrate a magnetism-driven transition between these phases.